(untitled) (Jurnal Teknodik, 2015)
Abstrak: Tulisan ini bertujuan untuk mendeskripsikan peran profesi pengembang teknologi pembelajaran di sekolah dalam mensukseskan pelaksanaan kurikulum 2013. Hasil kajian ini menunjukkan bahwa untuk menyukseskan pelaksanaan kurikulum 2013, maka perlu peran profesi atau jabatan fungsional pengembang teknologi pembelajaran untuk mengembangkan berbagai sistem atau model pembelajaran yang inovatif berbasis TIK. Selain itu, hasil kajian ini menunjukkan profesi pengembang teknologi pembelajaran dapat mengembangkan berbagai media dan sumber belajar berbasis TIK. Jadi untuk menyukseskan pelaksanaan kurikulum 2013 guru sangat memerlukan berbagai sistem atau model pembelajaran yang inovatif dan berbagai media dan sumber belajar berbasis TIK. Oleh karena itu, tugas dan peran profesi guru saling berkaitan dengan tugas dan peran profesi atau pejabat fungsional pengembang teknologi pembelajaran. Kata kunci: profesi, pembelajaran, pengembang teknologi pembelajaran, kurikulum 2013. Â Abstract: This paper aims to describe the role of professional development in instructional technology in the school curriculum of 2013, successful execution results of this study indicate that for the successful implementation of the curriculum in 2013, it is necessary functional role of the profession or occupation of instructional technology developers to develop a variety of systems or models of innovative ICT-based learning. In addition, the results of this study indicate the profession of instructional technology developers can develop a variety of media and learning resources ICT-based. So for the successful implementation of the 2013 curriculum teachers are in need of a variety of systems or models of innovative learning and a variety of media and learning resources ICT-based. Therefore, the task and the role of the teaching profession are related to the duties and role of the profession or functional official developer instructional technology. Key words: profession, learning, instructional technology developers, curriculum 2013.